PENGARUH GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP KINERJA KEUANGAN BANK KONVENSIONAL YANG TERDAFTAR DI BEI - Verda Nusantara; Djuwitawati Ratnaningtyas; Syarifah Ratih Kartika Sari (Universitas Merdeka Madiun, 2023)
This study aims to empirically examine the effect of good corporate governance, company size, and leverage on financial performance. The population in this study are conventional bank companies listed on the IDX in 2018 – 2021. This type of research uses quantitative methods. The sample in this study amounted to 33 out of 42 coventional bank populations. The method used in this research is multiple linear regression analysis using SPSS version 24 program. The results showed that independent commissioners affect financial performance, institusional ownership affects financial performance, audit committee affects financial performance, company size affects fincancial performance, and leverage affect financial performance.